Assessing the risk of cardiovascular events in patients receiving immune checkpoint inhibitors - Torrente, María; Blanco, Mariola; Franco, Fabio; Garitaonaindia, Yago; Calvo, Virginia; Collazo-Lorduy, Ana; Gutiérrez, Lourdes; Sánchez, Juan Cristóbal; González-del-Alba, Aranzazu; Hernández, Roberto; Méndez, Miriam; Cantos, Blanca; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Immune checkpoint inhibitors (ICIs) have revolutionized cancer treatment. However, despite their excellent therapeutic effect, these medications typically result in a broad spectrum of toxicity reactions. Immune-related cardiotoxicity is uncommon but can be potentially fatal, and its true incidence is underestimated in clinical trials. The aim of this study is to assess the incidence and identify risk factors for developing a cardiac event in patients treated with ICIs. Methods We conducted a single-institution retrospective study, including patients treated with ICIs in our center. The main outcomes were cardiac events (CE) and cardiovascular death. Results A total of 378 patients were analyzed. The incidence of CE was 16.7%, during a median follow-up of 50.5 months. The multivariable analysis showed that age, a history of arrhythmia or ischemic heart disease, and prior immune-related adverse events were significantly associated with CE. Conclusion CE during ICI treatment are more common than currently appreciated. A complete initial cardiovascular evaluation is recommended, especially in high-risk patients, being necessary a multidisciplinary approach of a specialized cardio-oncology team.